Implementasi Manajemen Sumber Daya Insani Dalam Meningkatkan Kinerja Karyawan BPRS Madina - Vero Kiki Zuliza; Dyah Pikanthi Diwanti (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the implementation of Islamic Human Resource Management (IHRM) in improving employee performance at PT BPRS Madina Mandiri Sejahtera Yogyakarta. The background of this research is based on the challenges faced by Islamic financial institutions in managing employees with non-Islamic educational backgrounds, while the bank has a strategic mission to disseminate Islamic economic principles. The gap between sharia competency demands and employees' educational backgrounds is a crucial issue that needs to be addressed through adaptive and inclusive IHRM strategies. This study employs a qualitative approach with a case study design, conducted at the head office of PT BPRS Madina Mandiri Sejahtera Yogyakarta. Data were collected through in-depth interviews with seven informants, participatory observation, and documentation. Data analysis used the interactive model by Miles et al. (2014). The results show that IHRM efforts in developing non-sharia employees are carried out through four dimensions: integrity-based inclusive recruitment, structured re-education, mentoring based on Ta'awun values, and spiritual value internalization. The implementation of these four IHRM functions proved to have a significant impact on  employe  performance  across  six  indicators:  quality,  quantity,  timeliness,